Students’ Perception of Project Based Learning in Writing Class - Fadhillah, Nurul; Sudjarwo, Sudjarwo; Habsari, Dwiyana (Lafadz Jaya Publisher, 2023)
The objective of this research was to find out students’ positive perceptions on the use of project-based learning in writing class. The project-based learning focused on the students’ perceptions and the benefits of their writing project. The data were collected through a questionnaire adapted from Unumeri, G.O (2009) and also interviews. The research method used a quantitative approach with descriptive statistic data analysis techniques. The subjects of this research were 60 senior high school students in SMA Qur’an Darul Fattah. The questionnaire results showed that most of the students had positive perceptions on the use of project-based learning. They agree that the material used in project-based learning is clear, interesting, and easy to understand. In addition, the use of project-based learning in learning activities can enhance their motivation and improve their writing skill. Furthermore, students have positive perceptions toward the teacher’s ability in guiding and facilitating them in project-based learning in writing class.